Optimal duration and timing of adjuvant chemotherapy after definitive surgery for ductal adenocarcinoma of the pancreas: ongoing lessons from the ESPAC-3 study - Valle, Juan W.; Büchler, Markus W. (Journal of clinical oncology, 2014)
Purpose Adjuvant chemotherapy improves patient survival rates after resection for pancreatic adenocarcinoma, but the optimal duration and time to initiate chemotherapy is unknown. Patients and Methods Patients with pancreatic ductal adenocarcinoma treated within the international, phase III, European Study Group for Pancreatic Cancer-3 (version 2) study were included if they had been randomly assigned to chemotherapy. Overall survival analysis was performed on an intention-to-treat basis, retaining patients in their randomized groups, and adjusting the overall treatment effect by known prognostic variables as well as the start time of chemotherapy. Results There were 985 patients, of whom 486 (49%) received gemcitabine and 499 (51%) received fluorouracil; 675 patients (68%) completed all six cycles of chemotherapy (full course) and 293 patients (30%) completed one to five cycles. Lymph node involvement, resection margins status, tumor differentiation, and completion of therapy were all shown by multivariable Cox regression to be independent survival factors. Overall survival favored patients who completed the full six courses of treatment versus those who did not (hazard ratio [HR], 0.516; 95% CI, 0.443 to 0.601; P < .001). Time to starting chemotherapy did not influence overall survival rates for the full study population (HR, 0.985; 95% CI, 0.956 to 1.015). Chemotherapy start time was an important survival factor only for the subgroup of patients who did not complete therapy, in favor of later treatment (P < .001). Conclusion Completion of all six cycles of planned adjuvant chemotherapy rather than early initiation was an independent prognostic factor after resection for pancreatic adenocarcinoma. There seems to be no difference in outcome if chemotherapy is delayed up to 12 weeks, thus allowing adequate time for postoperative recovery.
Gesehen am 24.09.2020